Constraints on color-flavor locked quark matter in view of the HESS J1731-347 measurement - Kourmpetis, Konstantinos; Laskos-Patkos, Pavlos; Moustakidis, Charalampos (HNPS Advances in Nuclear Physics, 2025)
Astrophysical observations play a crucial role in understanding the processes within compact stars. A recent study measured the central object in the HESS J1731-347 supernova remnant (SNR), estimating its mass at Μ=0.77 (+0.20, -0.17)Μο and radius at R = 10.40 (+0.86,-0.78)Mo km, identifying it as the lightest neutron star ever observed. Conventional models suggest neutron stars form with a minimum gravitational mass of approximately 1.17Mo, raising the question of whether this object is a typical neutron star or possibly an "exotic" star. To investigate, we utilize the Color-Flavor Locked (CFL) equation of state (EoS), integrating data from the HESS J1731-347 measurement with pulsar observations and gravitational wave detections. Additionally, we construct hybrid EoS by combining the MDI-APR1 (hadronic) and CFL (quark) EoS, introducing a phase transition through Maxwell construction. Our findings reveal that absolutely stable CFL quark matter effectively explains all observed measurements, including the central object of HESS J1731-347, whereas hybrid models incorporating the CFL MIT Bag model cannot account for the masses of the most massive observed pulsars.